E-Syariah : factors influencing innovation adoption in Malaysian islamic court administration. - Ramly, Norlida; Said, Mohd Fuaad; Ab. Rahman, Suhaimi; Choo , Wei Chong (2014)
Electronic Government usage is becoming common among Malaysian government agencies, however, an underutilized application could affect their successful operation. Thus, this article is to discuss on the importance of E-Syariah, a government to citizen (G2C) application in fulfilling the needs to improve Shariah Courts’ administration in Malaysia, and how the lacking of acceptance by its users, has a negative impact on its successful implementation. This article’s goal is to determine the factors that influence the use intention and actual usage of E-Syariah by Malaysian sharie lawyers. The research utilizes (Unified Theory of Acceptance and Use of Technology) UTAUT theory as a base to its research framework. A self administered questionnaire was used and responses from 240 sharie lawyers were collected and analyzed using structural equation modeling (SEM). The findings of the study indicate behavioral intention to use E-Syariah was positively influenced by performance expectancy and technical facilitating conditions; and use behavior of using E-Syariah was positively influenced by behavioral intention to use E-Syariah. This study can help Government of Malaysia evaluating their effort in implementing E-Syariah in specific and Electronic Government’s application in general.